Exploiting the potential of artificial intelligence techniques in FLT - Elena A. Maksimova; Galina А. Nikitina; Svetlana A. Shilova (Saratov State University, 2023)
The relevance of using artificial intelligence (AI) techniques in education has increased significantly during the pandemic and the forced transition to distance learning technologies. It was during this period that there was a breakthrough in the development of digital educational resources based on AI, but methodological support for their effective use was not prepared. The mechanisms of leveling the risks associated with possible effects of AI on education have not been identified. The objective: to identify the risks and potential of AI techniques in their impact on the organization and outcome of the educational process. Research methods: theoretical analysis and qualitative description of practical examples of the exploiting AI techniques in foreign language teaching. The research is based on the general literature review related to the key concepts of the study: artificial intelligence, digital educational resources, foreign language teaching. The results: the most widely used AI techniques are mobile applications and platforms with educational courses; the use of highly intelligent products, such as smart classrooms, is not sufficiently developed; the risks of implementing AI methods are associated with the quality of technology, with the methodological proficiency of a teacher, and with individual learning strategies. The conclusions: at the current level of technology development, AI techniques are a supplementary educational component. It is advisable to involve teachers of particular subjects in the further improvement of these technologies. The practical significance of the results obtained is determined by the assessment of the AI technologies impact on the process of FLT and by the proposed methods of effective use of AI in teaching.